2018
DOI: 10.1007/s40617-018-00296-4
|View full text |Cite
|
Sign up to set email alerts
|

Training Education Professionals to Use the Picture Exchange Communication System: a Review of the Literature

Abstract: The Picture Exchange Communication System (PECS) is a popular augmentative and alternative communication strategy. Like many communication interventions, the successful use of PECS is dependent on the skills of the communication partner. This article provides a systematic review of the published research on teaching education professionals (EPs) to use PECS. Training of EPs was usually conducted during individual or small group sessions and included a description of the PECS strategy, practice on implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Although, given the small number of participant-camp worker dyads for whom complete data were available, these results should be interpreted cautiously. These results are consistent with those of recent reviews that found that the majority of PECS implementers were able to achieve mastery criteria and improve the quality of PECS implementation following training (Alsayedhassan et al, 2016;McCoy & McNaughton, 2019). In addition to overall treatment fidelity, exploratory analyses examined the accuracy of teaching at different phases.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although, given the small number of participant-camp worker dyads for whom complete data were available, these results should be interpreted cautiously. These results are consistent with those of recent reviews that found that the majority of PECS implementers were able to achieve mastery criteria and improve the quality of PECS implementation following training (Alsayedhassan et al, 2016;McCoy & McNaughton, 2019). In addition to overall treatment fidelity, exploratory analyses examined the accuracy of teaching at different phases.…”
Section: Discussionsupporting
confidence: 85%
“…Encouragingly, those studies that did report fidelity reported high degrees of such (e.g., 98.6%; Tincani et al, 2006). In fact, recent reviews of PECS mediator training demonstrated that following training, the majority of PECS implementers achieved high treatment fidelity (Alsayedhassan et al, 2016) and demonstrated improvement in the quality of PECS implementation (McCoy & McNaughton, 2019). Importantly, a few studies have also presented data on treatment fidelity by PECS phase (e.g., Cummings et al, 2012;Martocchio & Rosales, 2016); however, this level of detail is rare, leaving gaps in understanding whether certain phases of PECS may be taught with higher or lower fidelity.…”
Section: IVmentioning
confidence: 99%
“…When the child is successful with the prior phase, the next phase of the PECS is introduced (Wong et al, ). Given the suspected effectiveness of the PECS (McCoy & McNaughton, ), there is little research that evaluates the effectiveness of the PECS when comparing a person who is trained and person who is not trained.…”
Section: Purpose Hypothesis and Research Questionsmentioning
confidence: 99%
“…Indeed, a corpus of studies from countries such as Australia, Canada, the United Kingdom, and the United States shows that the use of PECS among children with ASD is closely linked to better communication and positive behavior (5,6,10,(21)(22)(23). Some studies have demonstrated that the use of PECS among children with ASD enables them to engage in prolonged conversation, initiate conversation, and make demands, decisions, and choices (5,10,24,25). Furthermore, the use of PECS enables children with ASD to develop better or more positive behavioral skills that facilitate their inclusion in society (6,24,26).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the use of PECS among children with ASD enables them to engage in prolonged conversation, initiate conversation, and make demands, decisions, and choices (5,10,24,25). Furthermore, the use of PECS enables children with ASD to develop better or more positive behavioral skills that facilitate their inclusion in society (6,24,26). This clearly underscores the need for the practitioners and the parents to adopt PECS to enable non-verbal children with ASD to develop a form of language for communication.…”
Section: Introductionmentioning
confidence: 99%